The essential menopause curriculum for healthcare professionals: A European Menopause and Andropause Society (EMAS) position statement. (April 2022) - Rees, Margaret; Abernethy, Kathy; Bachmann, Gloria; Bretz, Silvia; Ceausu, Iuliana; Durmusoglu, Fatih; Erkkola, Risto; Fistonic, Ivan; Gambacciani, Marco; Geukes, Marije; Goulis, Dimitrios G.; Griffiths, Amanda; et al.
Highlights: Managing perimenopausal and postmenopausal health is a key issue for all areas of healthcare, not just gynecology. Training programs for healthcare professionals worldwide should include menopause and postmenopausal health in their curriculum. The curriculum should include assessment, diagnosis and evidence-based management strategies. Abstract: Introduction: The menopause, or the cessation of menstruation, is a stage of the life cycle which will occur in all women. Managing perimenopausal and postmenopausal health is a key issue for all areas of healthcare, not just gynecology. Aim: To provide recommendations for the curriculum of education programs for healthcare professionals worldwide, so that all can receive high quality training on menopause. Materials and methods: Literature review and consensus of expert opinion. Summary recommendations: Training programs for healthcare professionals worldwide should include menopause and postmenopausal health in their curriculum. It should include assessment, diagnosis and evidence-based management strategies.